Semi-Automatic 3D Modeling of Rooftop Types from Aerial Photos - Nursyahrial, Arsa Fa'iz; Ilmawan, Hanif (Universitas Gadjah Mada, 2025)
Urban planning has dynamic problem as time goes by. 3D City Model is one of solutions to help planners in decision making, because it can represent real objects in high detail, including the rooftop type. In this research, case study of 3D City Model located in the office area of Wonogiri Regency Government, which was processed from aerial photos using semi-automatic method with LoD 2 standart. This semi-automatic method used Computer Generated Architecture (CGA) rules that contained commands to create objects based on their input. The result was a 3D model of the building along with road and landscape. The roof shape of 3D building model was compared to aerial photos in order to evaluate the visual accuracy, specifically aiming for completeness, correctness, and accuracy values above 85%. The result showed that the flat and shed have the highest accuracy, while the gable roof has low accuracy, though they were all above 85% accuracy. This means that the semi-automatic method has potential for 3D modeling purpose in any kind of standart roof types.